2016
DOI: 10.1080/10495398.2016.1242489
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in IL8 and TLR4 Genes as Candidates for Digital Dermatitis Resistance/Susceptibility in Holstein Cattle

Abstract: Relatedness between single nucleotide polymorphisms in IL8 and TLR4 genes and digital dermatitis resistance/susceptibility was investigated in seventy Holstein dairy cows. Animals were assigned into two groups, affected group (n = 35) and resistant group (n = 35) based on clinical signs and previous history of farm clinical records. Blood samples were collected for DNA extraction to ampliy fragments of 267-bp and 382-bp for IL8 and TLR4 genes, respectively. PCR-DNA sequencing revealed three SNPs in each of IL8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This scenario favours the survival of T. pallidum in the hosts and prevents the removal of T. pallidum by strong inflammatory responses. Meanwhile, Tp92 induces the production of IL‐8, which causes the accumulation of neutrophils and lymphocytes to the site of infection, increases the degree of infiltration of inflammatory cells in the infected area, and aggravates the immunopathological damage of the site . On the other hand, IL‐8 promotes the release of elastase by neutrophils, damages endothelial cells, and facilitates the transport of T. pallidum across the endothelial barrier and into the blood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario favours the survival of T. pallidum in the hosts and prevents the removal of T. pallidum by strong inflammatory responses. Meanwhile, Tp92 induces the production of IL‐8, which causes the accumulation of neutrophils and lymphocytes to the site of infection, increases the degree of infiltration of inflammatory cells in the infected area, and aggravates the immunopathological damage of the site . On the other hand, IL‐8 promotes the release of elastase by neutrophils, damages endothelial cells, and facilitates the transport of T. pallidum across the endothelial barrier and into the blood .…”
Section: Discussionmentioning
confidence: 99%
“…62 The T. pallidum antigen TpF1 promotes the secretion of the anti-inflammatory factor IL-10 to resist elimination by inflammation. 63 Interestingly, further research showed that Tp92 64 On the other hand, IL-8 promotes the release of elastase by neutrophils, damages endothelial cells, and facilitates the transport of T. pallidum across the endothelial barrier and into the blood. 65 The TpF1 protein induces the secretion of IL-8 by hosts, promotes skin and mucosal vascular proliferation in patients with syphilis, increases vascular permeability, and helps the spread of T. pallidum throughout the body via the blood vessels.…”
Section: Control Rosup Tp92mentioning
confidence: 99%
“…Several polymorphisms have been identified in bovine TLR4 gene (White et al, ) which are reported to affect SCS, be associated with estimated breeding values for lactation persistency and also revealed an association of E3+2021 with milk fat and protein percentage in late lactation in Holstein‐Friesian, Jersey, Norwegian Red, Montbeliarde and Holstein‐Friesian × Jersey cows (Beecher et al, ; Sharma, Leyva, Schenkel, & Karrow, ; Wang, Xu, Gao, Ren, & Chen, ). Many studies reported the association between bovine TLR4 gene and somatic cell score and susceptibility/resistance of many dairy cow diseases (El‐Shafaey et al, ; Li et al, ; Noori et al, ); however, few literatures reported such association with reproductive performance traits (Goldammer et al, ; Shimizu et al, ; Werling & Jungi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in molecular genetics and development of molecular techniques have led to the discovery of genes, or markers associated with genes involved in economic traits (GAO et al, 2007;GHANEM et al, 2016). When a polymorphic locus is associated with the economic traits of animals, that polymorphic locus can therefore be used as a genetic marker for the trait and become useful as a selection criterion for genetic improvement of this trait (marker-assisted selection) (EL-SHAFAEY et al, 2017;ELDOMANY et al, 2019).…”
Section: Tlr4 Gene Expression Patternmentioning
confidence: 99%